Beyond performance : how great organizations build ultimate competitive advantage - Keller, Scott; Price, Colin (Hoboken, NJ : Wiley, 2011)
The secret of achieving and sustaining organizational excellence revealed In an ever-changing world where only a third of excellent organizations stay that way over the long term, and where even fewer are able to implement successful change programs, leaders are in need of big ideas and new tools to thrive. In Beyond Performance, McKinsey & Company's Scott Keller and Colin Price give you everything you need to build an organization that can execute in the short run and has the vitality to prosper over the long term. Drawing on the most exhaustive research effort of its kind on organizational.
Why Performance is not Enough. The Big Idea: Performance and Health -- The Science: Hard Facts behind the Soft Stuff -- The Five Frames. Aspire: Where Do We Want to Go? -- Assess: How Ready Are We to Go There? -- Architect: What Do We Need to Do to Get There? -- Act: How Do We Manage the Journey? -- Advance: How Do We Keep Moving Forward? -- Putting it all Together. The Senior Leader's Role: Does Change Have to Start at the Top? -- The Five Frames in Action: How Do You Make a Great Organization Even Better? -- Making It Happen: Do You Have What It Takes?
Keywords: Organizational behavior; Corporate culture; Performance; Corporate culture; Organizational behavior; Performance; Electronic resource